An Exploration of Moral Values in The Film of 2024 Indonesian Version of 'Annoying My Brother' - Muhammad Zidan Muharromi Lerebulan; Otong Setiawan; Andang Saehu (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study explores moral values in the 2024 Indonesian film My Annoying Brother through a literary sociology approach using C.S. Lewis' moral theory. The research employed a descriptive qualitative method by analyzing dialogue, characters, and conflicts in the film. The findings revealed 14 moral values: 2 spiritual, 5 personal, and 7 social values, all reflected in key scenes involving gratitude, responsibility, discipline, and compassion. These results highlight the film’s role not only as entertainment but also as a medium for moral education and social reflection. This research contributes to the study of moral representation in visual literature and supports the integration of ethical values in film narratives.